Sheep herd health and reproductive management associated with lamb weight gain and mortality in sub-Saharan drylands – a case from Ethiopia - Lysholm, Sara; Genfors, Elisabeth (Swedish University of Agricultural Sciences, 2023)
The dataset consists of a TSV file consisting of 209 rows and 54 columns and contains the following information: information about the herd and its localisation (type of village, village number, household number), information about the ewe (pseudonymized ID, age, number of lambs in total, number of lambs this litter, body condition score, presence of fleece contamination and presence of clinical signs of disease), information about the lamb (pseudonymized ID, sex, age at first weighing, number of siblings, weight at first weighing and presence of clinical signs of disease), and the weight of the lamb at one, two, three, four and five months of age. The body condition of the ewe is indicated using a five degree scale from 1 (very thin) to 5 (obese). The fleece contamination of the ewe is indicated using a four degree scale from 0 (clean fleece) to 3 (heavily contaminated fleece). The dataset contains information on the same herds as in dataset SND-ID: 2020-185.

Datasetet utgörs av en TSV-fil bestående av 209 rader och 48 kolumner innehållande följande information: information om flocken och dess lokalisation (typ av by, bynummer, hushållsnummer), information om tackan (pseudonymiserad ID, ålder, totalantal födda lamm, antal lamm i kullen, hullskala, förekomst av ullkontamination och förekomst av kliniska symtom på sjukdom), information om lammet (kön, pseudonymiserad ID, ålder vid första vägning, antal syskon, vikt vid första vägning och förekomst av kliniska symtom på sjukdom) samt lammets vikt vid ett, två, tre, fyra och fem månaders ålder. Tackans body condition score är baserad på en femgradig skala från 1 (kraftigt avmagrad) till 5 (kraftigt överviktig). Tackans grad av ullkontamination är baserad på en skala fyrgradig skala från 0 (helt ren) till 3 (kraftigt nedsmutsad). Datasetet beskriver samma flockar som datasetet SND-ID: 2020-185.
Fårflockhälsa och reproduktionsrutiner och deras association med lammtillväxt och -dödlighet i Etiopien
Keywords: Herd health; Flockhälsa; Reproductive health; Reproduktiv hälsa; Lamb health; Lammhälsa; Sheep; Får; Lamb weight gain; Lammtillväxt; Lamb mortality; Lammdödlighet; Lamb; Lamm; Veterinary Science; Veterinärmedicin